Nilai-Nilai Pendidikan Islam Damai dalam Novel “Bulan Terbelah di Langit Amerika” - Sarah, Siti; Munandar, Didih Syakir; Darisman, Dede (Tsamratul Fikri | Jurnal Studi Islam, 2019)
After researching the novel "Bulan Terbelah di Langit Amerika” (The Moon Ripped in the American Sky), found a number of values of peaceful Islamic education, namely: Aqeedah Education Values, Ubudiyah Education Values, and Values of Moral Education. So that the values of peaceful Islamic education are relevant to the current Islamic Religious Education, which must be applied are: religious attitudes as moral orientations, religious attitudes in internalizing religious values, and religious attitudes as work ethics and social skills. These three values are very important and can elevate human degrees in the eyes of Allah. and in other human eyes. Positive morals such as tolerance are the main key to creating a peaceful life. So that with the values of Islamic education that exist or with positive morals, Islam can reconcile the world and be realized in real life